Studi Perbandingan Mocaf dengan Tepung Hanjeli (Coix Lacryma Jobi L.) Terhadap Karakteristik Sponge Cake Gluten Free - Hariputeri, Hossiana; Wiadnyani, Anak Agung Istri Sri; Suparthana, I Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 1 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i01.p12, 2024)
Sponge cake is a type of pastry product that is widely consumed because of its soft and light texture, and sponge-like shape. The basic ingredient for making sponge cake is wheat flour, but wheat imports are high and not everyone can tolerate gluten. Mocaf can be used as a flour substitute however mocaf-based sponge cake have a low protein levels. Therefore, it is necessary to add other ingredients such as adlay flour to increase the protein content in the sponge cake. The aim of this study was to determine the effect different mocaf and adlay flour ratios have on sponge cake characteristics as well as to determine the ideal ratio to produce sponge cake with the most favorable attributes. The study used completely randomized design (CRD), with the treatment of the ratio of mocaf to adlay flour 100:0, 90:10, 80:20, 70:30, 60:40, and 50:50 repeated 3 times which resulted in 18 experimental units. Data were analyzed using Analysis of Varians (ANOVA) and further analyzed using Duncan Multiple Range Test if the treatment had a significant effect. The results showed that different ratios produced significant effect (P <0.05) on moisture, protein, fat, carbohydrate and crude fiber contents, texture and baking expansion, and product sensory properties, but had no significant effect (P>0.05) on product ash content. The best sponge cake was produced when mocaf and adlay flour were combined in a 60:40 ratio, which had a moisture content of 36.89%, ash of 0.89%, protein of 7.07%, fat of 27.45%, carbohydrate of 27.7%, texture of 1.2 N, baking expansion of 39.81%, with color liked, aroma somewhat liked, taste liked, texture liked, and overall acceptance liked by panelists.